Development of an EMI Course with the Integration of Innovative Methods: Effects on Students’ Confidence, Knowledge, and Skills - Chu, Curtis; Takahashi, Mariko (Journal of Interdisciplinary Studies in Education, 2024)
While various innovative pedagogical methods have been proven effective in facilitating the development of students’ English language skills under different contexts, this study explores the implementation of several innovative methods into one EMI course, which includes Collaborative Online International Learning (COIL), Content Language Integrated Learning (CLIL), Problem Posing Education (PPE), and Project Based Learning (PBL). Deliberate considerations were made to the choice and implementation of the innovative methods: using COIL to stimulate motivation; CLIL and PPE to promote content learning (input); and PBL to facilitate content-integrated learning outcome (output). The effects of the course implementation were assessed by evaluating the course participants’ confidence, knowledge, and skills related to the use of English for communicative purposes. Data was gathered using pre- and post-course questionnaires containing self-evaluated quantitative and open-ended qualitative questions. Based on the results from the 24 participants in the course, it was found that the course was highly effective in promoting the development of the participants’ confidence, knowledge, and skills with large effect sizes. In addition, from students’ feedback on the course, their expectations for the course were met, and the course objectives were achieved. Utilizing innovative methods strongly contributed to the positive outcomes of the course.